ANALYSIS OF THE PROBLEM SOLVING METHOD ABILITY IN THE SUBJECT OF PLANE GEOMETRY FOR 6TH GRADE ELEMENTARY SCHOOL - Unaenah, Een; Istikharah, Marshanda; Aisyah R., Nabilla; Heruni, Qulu Bunur (Transpublika Publisher, 2023)
The reason for this review is to make sense of the different difficulties looked by understudies while taking care of word issues connected with level shape material in grade VI utilizing the critical thinking strategy. Critical thinking technique As indicated by polya, which comprises of four phases: 1). Having an understanding of the issue Plan a way to solve problems (step 3). Implement the plan for solving problems (4). Verify the work's results once more. Measurements made of students and teachers in Class VI served as the foundation for this study. Understudies direct meetings, documentation, and perceptions, while educators lead interviews. As a result, the goal of this study was to find out how well sixth-grade students could olve problems using flat-shaped materials. The exploration results cover different kinds of hardships, for example, trouble figuring out, causal elements, and exertion. Working on a measurement of the story material also presents challenges; for instance, students struggle to identify questions, count, and draw conclusions. Factors causing trouble comprise of individual variables for every understudy connected with their review propensities, dominance of the material, and instructor help factors. Communicating the issues that were encountered, using communicative language to create story questions, frequently engaging in exercises, expanding the knowledge gained from solving story problems, employing responsive and contextual learning, offering individual guidance, providing motivation and rewards, and making use of learning media are all examples of these methods. That is every one of the instructor's endeavors that should be possible